Francisco José de Abreu Matos: vida escolar, ensino, pesquisa e extensão em fatos, documentos e fotos (1924 - 2008) - Marques, Karina Martins (2016)
This research aims to understand from facts, documents and photos, as unfolded the life and work of Professor Francisco José de Abreu Matos, presenting his school life, his teaching career at the Faculty of Pharmacy and Dentistry of Ceará later as professor at the University of Ceará, but also their scientific research and its extension projects in the 1924-2008 period. Coming from a family that pharmaceutical form generations, would be the greatest researcher cearense regarding Medicinal and Aromatic Plants of the Northeast, project linked to the Natural Products Laboratory of the Federal University of Ceará - UFC. It was discoverer of hundreds of species of flora and northeastern and lends his name to the nomenclature of these plants. He was the creator of the Living Pharmacy Project that has spread across the country. His journey through teaching, research and extension has always been guided by social work, which he saw as a matter of habit, to democratize the access of the poor to herbal medicines population. The Living Pharmacy Project is the result of the will of a researcher, teacher, idealist and foremost a citizen aware of their role in society. For dreamed, she ran to put into practice a desire, the desire to bring the people a pharmaceutical social assistance program.